Investments in Gas Pipelines and Liquefied Natural Gas Infrastructure. What is the Impact on the Security of Supply? - Patrick Cayrade (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper addresses the question of the infrastructure investment required for gas pipeline and liquefied natural gas (LNG) connections to meet growing gas demand in an enlarged EU over the next 20 years. Several issues are presented, bearing in mind the major objective of the security of supply for EU countries. First, to set the scene, recent projections of gas demand in an enlarged EU are presented along with the corresponding need for additional imports. Then a scenario is developed showing possible supply routes to meet the import gap, relying on increasingly remote routes. An impressive bill of 150 to 200 billion will have to be paid for extending and building the required infrastructure in pipeline links and LNG-receiving facilities. The expected major development of LNG markets is subject to a particular discussion, as far as the progressive globalisation of this market and its inherent flexibility provide major advantages in terms of the security of supply, despite more costly infrastructure than pipeline links. The impact of technological progress is expected to reduce both capital investment and unit transport costs, offering access to new supply opportunities. Finally, the question of major obstacles to the realisation of the required huge investments in gas infrastructure over the next 20 years is addressed, opening hot debate on the subjects of future gas price, market liberalisation and financing issues.
Keywords: Q41; Q43; 330; Investment; Gas pipelines; Liquefied natural gas; Security of supply; Energieversorgung; Erdgasmarkt; Energieinfrastruktur; Flüssiggas; Welt